PENGARUH SALURAN PENJUALAN DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN (Studi Kasus Pabrik Tahu Bapk Tarwoto di Nagari Kurnia Selatan, Kec. Sungai Rumbai) - Ike Frandika Wibowo; Yesi Gusteti; Kelik Purwanto (Universitas Sarjanawiyata Tamansiswa, 2022)
Researchers want to see how far the influence of sales channels and product quality on customer loyalty. This study was conducted to find out and analyze what kind of influence is caused by sales channels and product quality on customer loyalty at the tofu factory of Mr. Tarwoto. The purpose of this study was to determine and analyze